Hubungan Antara Indeks Massa Tubuh (IMT) dan Lingkar Lengan Atas (LILA) dengan Kadar Gula Darah dan Kolesterol pada Wanita Usia Subur (WUS) di Kecamatan Cangkringan Kabupaten Sleman - Dwi R, Desy Hadi; , Mutalazimah, SKM., M.Kes; , Dyah Widowati, SKM (2013)
Introduction: Some women of childbearing age who have an impact on the health of individuals suffering from an illness. On the other hand there is a tendency WUS excess cholesterol due to lifestyle and diet is wrong. Cholesterol blood sugar levels and can be identified by measuring BMI and UAC. Objective: To investigate the relationship between Body Mass Index (BMI) and Upper Arm Circumference (UAC) and blood sugar and cholesterol level in women of childbearing age at Cangkringan, Sleman regency. Methods: This research uses analytic survey research with cross sectional approach. This research was conducted in the District Cangkringan, Sleman regency. The population in this study were all women of child bearing age in Cangkringan, Sleman regency which totaled 4937. Size of the sample as many as 26 people. Sampling techniques in this research is to use multi-stage random sampling method. Conclusions: 1) There was not any between BMI and blood sugar level, 2) There was not any between BMI and cholesterol, 3) There was not any between UAC and blood sugar level, 4) There was not any between UAC and cholesterol..